2012
DOI: 10.1016/j.sjbs.2011.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Consequence of the antioxidant activities and tyrosinase inhibitory effects of various extracts from the fruiting bodies of Pleurotus ferulae

Abstract: This study was initiated to screen the antioxidant activities, tyrosinase inhibitory effects on the fruiting bodies of Pleurotus ferulae extracted with acetone, methanol and hot water. The antioxidant activities were performed on β-carotene-linoleic acid, reducing power, DPPH, ferrous ions chelating abilities, and xanthine oxidase. In addition to this, phenolic compounds were also analyzed. The methanolic extract showed the strongest β-carotene-linoleic acid inhibition and high reducing power as compared to ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 28 publications
0
44
1
1
Order By: Relevance
“…P.Kumm. (Alam et al, 2010;Hapsari et al, 2012) and Pleurotus salmoneostramineus Vassil . Although Pleurotus species are the most studied mushroom species with reported anti-tyrosinase potential, none of those studies were able to identify the bioactive metabolites responsible for this activity.…”
Section: Anti-tyrosinase Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…P.Kumm. (Alam et al, 2010;Hapsari et al, 2012) and Pleurotus salmoneostramineus Vassil . Although Pleurotus species are the most studied mushroom species with reported anti-tyrosinase potential, none of those studies were able to identify the bioactive metabolites responsible for this activity.…”
Section: Anti-tyrosinase Activitymentioning
confidence: 99%
“…Other Pleurotus species with reported anti-tyrosinase activity are Pleurotus ferulae Quél. (Alam et al, 2012); Pleurotus nebrodensis (Inzenga) Quél. ; Pleurotus ostreatus (Jacq.…”
Section: Anti-tyrosinase Activitymentioning
confidence: 99%
“…Pleurotus ferulae (PF) is an edible mushroom with high nutritional value and significant pharmacological properties, which grows on the living rhizome trunks of Ferula asafoetida in the Gobi desert and is mainly distributed in Xinjiang, China. PF produces various biologically functional components and exerts anti-oxidant, antitumor, and anti-microbial activities [18][19][20]. Recently, our study showed that PF ethanol extract (PFEC) suppressed tumor growth through induction of cell apoptosis, and inhibition of cell proliferation and migration [21].…”
Section: Introductionmentioning
confidence: 99%
“…Higher Tb.BMD, BV/TV and Tb.Th and lower BS/BV in NPM mice compared with OVX mice are also in agreement with another study in which nonirradiated Pleurotus mushroom extracts were shown to alleviate the decrease in Tb.BMD in osteoporotic mice [36]. P. ferulae contains various phenolic and flavonoid compounds [37], as well as phytochemicals that have been shown to elicit a bone-protective effect [31,38,39].…”
Section: Discussionmentioning
confidence: 99%